2000
DOI: 10.1080/00050060008260334
|View full text |Cite
|
Sign up to set email alerts
|

Encounters with the dominant culture: Voices of indigenous students in mainstream higher education

Abstract: Students from minority and nondominant backgrounds often have negative experiences when dealing with higher education systems. In this study we explored Indigenous student's experiences in mainstream higher education. Interviews were conducted with 34 participants, systematically selected from a listing of 110 past and present students, about their experiences in mainstream higher education. Participants included people who had successfully completed programs at Curtin University of Technology, those who did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
1
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 30 publications
0
62
1
5
Order By: Relevance
“…Desse modo foi possível constatar algumas tentativas de ampliação dessa perspectiva de maneira a abordar problemas e benefícios da implantação de modelos vigentes, fornecendo uma visão crítica voltada para a necessidade de se pensar identidades sociais em suas especificidades étnicas (Sonn, Bishop & Humphries, 2000).…”
Section: As Três Unidades De Análiseunclassified
See 1 more Smart Citation
“…Desse modo foi possível constatar algumas tentativas de ampliação dessa perspectiva de maneira a abordar problemas e benefícios da implantação de modelos vigentes, fornecendo uma visão crítica voltada para a necessidade de se pensar identidades sociais em suas especificidades étnicas (Sonn, Bishop & Humphries, 2000).…”
Section: As Três Unidades De Análiseunclassified
“…Outros estudos trouxeram relatos de estudantes beneficiados pelas cotas, os quais denunciaram o falso discurso de igualdade e democracia racial vigentes atualmente, sobretudo, nas universidades norte-americanas, sendo o mesmo utilizado de maneira estereotipada e pouco vista na prática (Sonn et al, 2000). Foram levantadas questões sobre alternativas para facilitar o processo de internalização da tolerância diante das diferenças em contraposição à anulação do arsenal simbólico, isto é, a padronização cultural e racial da reincidente sociedade colorblind (Bollinger, 2003).…”
Section: As Três Unidades De Análiseunclassified
“…In one of my research projects with indigenous students in mainstream higher education it was found that participants criticized psychology and other social sciences as culturally inappropriate and oppressive (Sonn, Bishop, & Humphries, 2000). Participants commented:…”
Section: Indigenous Writing: Challenges To Notions Of Self and Dominamentioning
confidence: 99%
“…As asserted, the Western knowledge paradigm that underpins the administration, management, research and teaching that occurs in most higher education institutions in Australia rarely aligns with Indigenous student epistemologies and ontologies (Sonn et al 2007) and tends to dismiss concerns about Indigenous sovereignty (McCarty et al 2005;McCarty and Lee 2014). There is little doubt that Indigenous Support Units have played a pivotal role in addressing this divide (Andersen et al 2008;Trudgett 2009;Behrendt et al 2012).…”
Section: Epistemological and Ontological Dissonancementioning
confidence: 99%